0 рейтинг
26 видели

упрастите выражение :

х( в квадрате) + 2х - (х + 1 ) ( в квадрате ) =

6а-1-(а+3)(в квадрате ) =

от (12 баллов) в разделе Алгебра | 26 видели

2 Ответов и Решений

0 рейтинг

х( в квадрате) + 2х - (х + 1 ) ( в квадрате ) =2x-1

6а-1-(а+3)(в квадрате ) =4a+10

 

от (42 баллов)
0 рейтинг

х( в квадрате) + 2х - (х + 1 ) ( в квадрате ) = x(в квадрате) + 2x - x(в квадрате) -2x - 1= -1

6а-1-(а+3)(в квадрате ) =6a-1-a(в квадрате) - 6a - 9= -10 - a(в квадрате)

от (26 баллов)
10,984,878 заданий
13,471,016 решений
8,518,553 комментариев
4,909,216 пользователей